Outcomes of retroperitoneal fibrosis-related hydronephrosis and its risk factors for poor prognosis: a multi-center retrospective cohort study in Chinese patients - Liu, Hongyan; Gao, Hui; Zhao, Jin-xia; Wong, Ut-kei; Liu, Shi-bo; Liu, Jian; Zhang, Ge; Wang, Kuan-ting; Wang, Yan; Zhao, Lin; Ma, Xiang-bo; Lu, Yue-wu; et al. (Frontiers in Medicine, 2024)
Retroperitoneal fibrosis (RPF) is a rare disease, characterized by the presence of a fibroinflammatory tissue that surrounds the abdominal aorta and the iliac arteries, and often entraps the ureters. Hydronephrosis is common complication of RPF, however, its clinical features and outcomes has not been well elucidated. Methods A total of 115 PRF related with hydronephrosis patients were recruited from 9 clinical centers in China since March 2010. They were followed up until death or September 2021, whichever came first.The mean age at diagnosis was 58.83±12.13 years and 80 patients (69.57%) were male. The median disease duration was 3.00 (1.00, 9.00) months. Renal impairment was observed in 88.35% patients and 49.57% showed bilateral ureteral involvements. Elevated ESR and CRP were presented in 80.28% and 62.02%. 28.21% (11/39) had increased IgG4 level and 41.38% (12/29) showed pathological IgG4 staining positive (IgG4 + /IgG + ≥40% or IgG4 + ≥10/HPF). Among them, 3 patients can be diagnosed as IgG4RD. After 60.43±34.53 months follow up, 36 patients had poor prognosis, which was associated with severe kidney impairment, bilateral hydronephrosis and inflammation status (elevated ESR and IgG) at diagnosis by case control study. eGFR and creatinine were independent risk factors after adjusting for all other significant associations (p=0.002, p=0.067 respectively). Glucocorticoid based therapy could reduce time of stenting, decrease the need of longterm ureteral stenting/ percutaneous nephrostomy (PNS)/ ureterolysis, increase the rate of mass shrinkage and reduce the new requirement of hemodialysis than surgery only strategy for RPF related hydronephrosis patients in the need of renal drainage, but did not reduce new onset renal atrophy.Conclusions Severity of kidney dysfunction and inflammation status were related with poor prognosis of hydronephrosis induced by RPF. More efficient interventions and strategies are needed for improving outcomes further.